(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Technology" refers to the use of science for practical reasons. The field of "green technology" encompasses a rapidly growing ommunity of techniques and materials, ranging from energy generation tactics to non-toxic cleaning solutions. This article also focuses on the same subject of green technology and its many applications, but in greater depth or in a more diagrammatic manner, such as an overview of green technology, which includesthe definition of green technology and the numerous kinds of green technology (Ocean Energy, Solar Energy and Wind Energy etc.). This paper also discusses the various advantages and disadvantages of green technology (such as sewage treatment, capture and storage technology, renewable energies, solid waste treatment and management, and water treatment), as well as the various applications of green technology (such as sewage treatment, capture and storage technology, renewable energies, solid waste treatment and management, and water treatment). Using environmentally friendly technologies Companies and utility providers are taking the necessary measures and exerting considerable effort to meet societal needs with long-term solutions that may be utilized now and in the future without creating environmental harm or depletion.